Imaging hydrogen oxidation activity of catalyst-coated perfluoro sulfonic acid-polymer electrolyte membranes using scanning electrochemical microscopy - Parthasarathy, Meera; Pillai, Vijayamohanan K. (Journal of Chemical Sciences, 2009)
Scanning Electrochemical Microscopy (SECM) is a unique technique for studying fast heterogeneous kinetics and to map reactivity gradients along the surface of an electrocatalyst, especially when it involves multiple surface sites of varying reactivity. It combines the dual advantages offered by ultramicroelectrode (UME) voltammetry in terms of reduced ohmic drop and insignificant double layer charging contribution with the advantages of imaging by rastering the UME across an electro-active surface. In this work, we demonstrate these distinctive features of SECM in evaluating reactivity gradients on catalyst (Pt/C) coated NafionA (R) films towards hydrogen oxidation activity, a reaction of immense technological relevance. Imaging has been performed in the feedback mode by allowing H(2) evolution at the tip (25 A mu m Pt UME), which is reoxidized at the substrate electrode containing Pt/C-Nafion film. Interesting distribution in H(2) oxidation activity has been observed as a function of potential applied to the Pt/C-Nafion film. In addition, a plot of normalized tip current versus the substrate electrode potential indicates the effect of potential-induced reactivity change in the catalyst-coated membranes. The results of the present investigation are believed to be useful to H(2)/O(2) PEM fuel cells with respect to evaluating reactivity gradients of catalyst-coated polymer electrolyte membranes, which is important to rectify problems related to catalyst utilization.
Keywords: hydrogen oxidation; Imaging; Nafion; platinum; SECM

Selective binding of benzoquinone with a Pt-II-cyclophane constructed on the skeleton of N,N `-bis(salicylidene)-p-phenylenediamine: synthesis and spectroscopic studies - Kumari, Niraj; Prajapati, Rishikesh; Dixit, Mudit; Mishra, Lallan (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2009)
The Schiff base NN'-bis(salicylidene)-p-phenylenediamine has been complexed with Pt(en)Cl-2 and the resulting Pt-II-cyclophane, [Pt(en)L](2)center dot 4PF(6), reacted with phenol, resorcinol, hydroquinone or benzoquinone in DMSO solution. Their binding has been monitored by the variation in the corresponding UV-visible and emission spectral patterns. The binding properties are compared with the earlier reported Zn-II-cyclophane [Zn(bpy)L](2) (bpy = 2,2'-bipyridine). A few solid adducts of phenol and benzoquinone with the Pt-II-cyclophane complex and hydroquinone as well as that of resorcinol with the Zn-cyclophane have also been synthesized and characterized.
Keywords: Coordination chemistry; Cyclophanes; Metallocyclophanes; platinum; Schiff bases

Renewable H-2 from glycerol steam reforming: effect of La2O3 and CeO2 addition to Pt/Al2O3 catalysts. - Montini, Tiziano; Singh, Rakesh; Das, Piyali; Lorenzut, Barbara; Bertero, Nicolas; Riello, Pietro; Benedetti, Alvise; Giambastiani, Giuliano; Bianchini, Claudio; Zinoviev, Sergey; Miertus, Stanislav; Fornasiero, Paolo (Chemsuschem, 2010)
Glycerol is the main byproduct of biodiesel production and its increased production volume derives from the increasing demand for biofuels. The conversion of glycerol to hydrogen-rich mixtures presents an attractive route towards sustainable biodiesel production. Here we explored the use of Pt/Al2O3-based catalysts for the catalytic steam reforming of glycerol, evidencing the influence of La2O3 and CeO2 doping on the catalyst activity and selectivity. The addition of the latter metal oxides to a Pt/Al2O3 catalyst is found to significantly improve the glycerol steam reforming, with high H-2 and CO2 selectivities. A good catalytic stability is achieved for the Pt/La2O3/Al2O3 system working at 350 degrees C, while the Pt/CeO2/Al2O3 catalyst sharply deactivates after 20 h under similar conditions. Studies carried out on fresh and exhausted catalysts reveal that both systems maintain high surface areas and high Pt dispersions. Therefore, the observed catalyst deactivation can be attributed to coke deposition on the active sites throughout the catalytic process and only marginally to Pt nanoparticle sintering. This work suggests that an appropriate support composition is mandatory for preparing high-performance Pt-based catalysts for the sustainable conversion of glycerol into syngas.
Keywords: biofuels; Glycerol; heterogeneous catalysis; platinum; supported catalysts

Extracellular biosynthesis of platinum nanoparticles using the fungus fusarium oxysporum - Syed, Asad; Ahmad, Absar (Colloids and Surfaces B-Biointerfaces, 2012)
Nanoscience is a blooming field and promises a better future. In order to fabricate nanoparticles in an eco-friendly and inexpensive manner, significant efforts are being made to replace the chemical and physical methods currently being used with the biological methods. Chemical methods are toxic while the physical ones are very expensive. Biological methods, apart from being cost-effective, also provide protein capped nanoparticles which are thus very stable, have good dispersity and do not flocculate, and may find use in various applications. The present work emphasizes on platinum nanoparticles synthesis protocol which occurs at ambient conditions. The fungus Fusarium oxysporum when incubated with hexachloroplatinic acid (H2PtCl6) in ambient conditions reduces the precursor and leads to the formation of stable extracellular platinum nanoparticles. The biosynthesis of platinum nanoparticles was monitored by UV-visible spectroscopy and these nanoparticles were completely characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The nanoparticles are in the size range of 5-30 nm and are stabilized by proteins present in the solution. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, fungal-based method for the synthesis of nanoparticles over a wide range of chemical compositions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Fungus; Nanoparticles; platinum

Pt States in BaCe0.98Pt0.02O3-delta during start up and shut down operations under different conditions: stability and activity of ionic Pt in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Catalysis Letters, 2014)
Stability of Pt species in doped BaCeO3 perovskites under Water gas shift reaction conditions is studied using X-ray absorption spectroscopy and in situ powder X-ray diffraction. The catalyst BaCe0.98Pt0.02O3-delta has Pt in +2 oxidation state and is found to be stable in the ionic form under reaction conditions as well as under various highly reducing shut down and start up conditions. In-situ XRD under Water Gas shift reaction conditions also reveals the Pt ions to be highly stabilized in lattice and no egress is observed.
Keywords: BaCeO3; Deactivation; platinum; WGS reaction; XPS

CoSe2 supported on nitrogen-doped carbon nanohorns as a methanol-tolerant cathode for air-breathing microlaminar flow fuel cells - Unni, SreeKuttan M.; Mora-Hernandez, Juan M.; Kurungot, Sreekumar; Alonso-Vante, Nicolas (Chemelectrochem, 2015)
The synthesis of CoSe2 nanoparticles supported on nitrogendoped carbon nanohorns (CoSe2/NCNH) and the influence of the interaction of the metal centre with the NCNH on the oxygen reduction reaction (ORR) are reported. CoSe2/NCNH shows a 50 mV lower onset overpotential and a 150 mV positive shift in the half-wave potential compared to CoSe2 supported on carbon and carbon nanohorns. This suggests that the intrinsic activity and the density of active reaction centres of CoSe2 are modified by NCNHs. An air-breathing direct meth-anol microlaminar flow fuel cell (mLFFC) is constructed using CoSe2/NCNH as a methanol-tolerant cathode catalyst. A maximum power density of 10.05 mWcm(-2) and a maximum current density of 124.20 mAcm(-2) are achieved with CoSe2/NCNH compared to the non-doped catalyst, CoSe2/C and Pt/C with 5m methanol as the fuel. The improved activity of CoSe2/ NCNH is attributed to the peculiar morphology and the nitrogen doping of the carbon nanohorns. This catalyst could be a suitable alternative to Pt.
Keywords: carbon nanohorns; chalcogenides; fuel cells; oxygen reduction reaction; platinum

Electrocatalysis of oxygen reduction reaction on shape-controlled pt and pd nanoparticles-importance of surface cleanliness and reconstruction - Devivaraprasad, Ruttala; Nalajala, Naresh; Bera, Bapi; Neergat, Manoj (Frontiers in Chemistry, 2019)
Shape-controlled precious metal nanoparticles have attracted significant research interest in the recent past due to their fundamental and scientific importance. Because of their crystallographic-orientation-dependent properties, these metal nanoparticles have tremendous implications in electrocatalysis. This review aims to discuss the strategies for synthesis of shape-controlled platinum (Pt) and palladium (Pd) nanoparticles and procedures for the surfactant removal, without compromising their surface structural integrity. In particular, the electrocatalysis of oxygen reduction reaction (ORR) on shape-controlled nanoparticles (Pt and Pd) is discussed and the results are analyzed in the context of that reported with single crystal electrodes. Accepted theories on the stability of precious metal nanoparticle surfaces under electrochemical conditions are revisited. Dissolution, reconstruction, and comprehensive views on the factors that contribute to the loss of electrochemically active surface area (ESA) of nanoparticles leading to an inevitable decrease in ORR activity are presented. The contribution of adsorbed electrolyte anions, in-situ generated adsorbates and contaminants toward the ESA reduction are also discussed. Methods for the revival of activity of surfaces contaminated with adsorbed impurities without perturbing the surface structure and its implications to electrocatalysis are reviewed.
Keywords: Adsorption; Dissolution; oxygen reduction reaction; Palladium; platinum; reconstruction; shape-control; surface cleaning

Can half-a-monolayer of pt simulate activity like that of bulk pt? solar hydrogen activity demonstration with quasi-artificial leaf device - Bajpai, Himanshu; Patra, Kshirodra Kumar; Ranjan, Ravi; Nalajala, Naresh; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2020)
Pt is the best cocatalyst for hydrogen production. It is also well-known that the surface atomic layer is critical for catalysis. To minimize the Pt content as cocatalyst, herein we report on half-a-monolayer of Pt (0.5 theta(Pt)) decorated on earth-abundant Ni-Cu cocatalyst, which is integrated with a quasiartificial leaf (QuAL) device (TiO2/ZnS/CdS) and demonstrated for efficient solar hydrogen production. For the QuAL, TiO2 is sensitized with ZnS and CdS quantum dots by the SILAR method. The 0.5 theta(Pt)-decorated Ni-Cu shows an onset potential of 0.05 V vs reversible hydrogen electrode for the hydrogen evolution reaction, which is almost similar to that of commercial Pt/C. Photoactivity of the present QuAL device with either bulk Pt or 0.5 theta(Pt)-coated Ni-Cu cocatalyst is, surprisingly, equal. Our findings underscore that a fraction of a monolayer of Pt can enhance the activity of the cocatalyst, and it is worth exploring further for the high activity associated with atomic Pt and other noble metals.
Keywords: artificial leaf; nickel-copper; Photocatalysis; platinum; Solar hydrogen